Interpretation Of Permission To Fight Kafir People In The Qur'an Surah Al-Hajj Verse 39 (A Reading of Hans George Gadamer's Hermeneutics) - Ainuki Astna Asysyifa; Munawir (al-Afkar, Journal For Islamic Studies, 2023)
The Qur'an is a book that must be understood properly and correctly because of its position as a guide for human life. In the process of understanding it, it cannot only be fixed on textual things, but must look at the context that includes the Qur'an. This is so that the Qur'an can be used as a guide that is not limited by time and space, which is suitable in all ages. Some verses of the Qur'an if only understood textually, there will be divisions and acts of violence, for example in Qs. Al-Hajj verse 39 which is one of the legitimacy of radicals to commit acts of violence. Gadamer's hermeneutics with the four concepts offered became one of the blades used to interpret Qs. Al-Hajj verse 39. The author takes two concepts from the four offered, namely the melting of horizons (text, author, reader) and application. Departing from Qs. Al-Hajj verse 39 which is interpreted using Gadamer's Hermeneutics, the author assumes that the verse emphasizes the values of peace and freedom in religion.